2016
DOI: 10.1136/bmjqs-2015-005092
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of online repositories of quality improvement projects, interventions and initiatives in healthcare

Abstract: With growing interest in sharing and spreading best practices and increasing reliance on QI as a key contributor to health system performance, the role of QI repositories is likely to expand. Designing future QI repositories based on knowledge of the range and type of features available is an important starting point for improving their usefulness and impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Empirical evidence on selective outcome reporting has primarily been obtained from RCTs as study protocols are made available in the trial registration process [4]. Calls for prospective registration of study protocols of observational studies have been made [30] and repositories of quality improvement projects are emerging [31]. HSR and quality improvement communities will need to consider and evaluate the feasibility and values of adopting these practices.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence on selective outcome reporting has primarily been obtained from RCTs as study protocols are made available in the trial registration process [4]. Calls for prospective registration of study protocols of observational studies have been made [30] and repositories of quality improvement projects are emerging [31]. HSR and quality improvement communities will need to consider and evaluate the feasibility and values of adopting these practices.…”
Section: Discussionmentioning
confidence: 99%
“…1 Stakeholders in our interviews generally supported registration of HSDR, albeit with some reservations, and quality improvement projects and implementation studies were identified as being potentially at high risk of these bias. As repositories of quality improvement projects emerge, 100 HSDR and quality improvement communities will need to consider and evaluate the feasibility and values of adopting these practices for studies of varied types and purposes.…”
Section: Overall Learning From the Project And Study Limitationsmentioning
confidence: 99%
“…7 Accordingly, only a fraction of QI projects implemented in practice are reported in peer-reviewed journals. 8 There are some online QI reporting repositories to disseminate learning, however, variation in the classification of projects makes comparisons difficult. 8 Furthermore, while the Standards for Quality Improvement Reporting Excellence guidelines advise to report costs, 9 barriers to this include disparate and limited formal guidance for improvement teams on the measurement of costs associated with QI, Open access and the accessibility of organisational and patient cost data.…”
Section: Introductionmentioning
confidence: 99%
“…8 There are some online QI reporting repositories to disseminate learning, however, variation in the classification of projects makes comparisons difficult. 8 Furthermore, while the Standards for Quality Improvement Reporting Excellence guidelines advise to report costs, 9 barriers to this include disparate and limited formal guidance for improvement teams on the measurement of costs associated with QI, Open access and the accessibility of organisational and patient cost data. 7 10-15 To support effective decision-making, robust information is required about the content and context of QI initiatives, the expected outcomes, initial costs of implementation and the subsequent impact on longterm costs for the health service.…”
Section: Introductionmentioning
confidence: 99%